The impact of service quality dimensions on students’ satisfaction: a study of international students in Malaysian public universities - Alade Najimdeen, Abdul Hakeem; Amzat, Ismail Hussein; Mohd Ali, Hairuddin (IIUM Press, 2021)
This study is conducted to examine the relationship between quality service and students’ satisfaction based on the perceptions of international students in Malaysian public universities. The questionnaire used was adapted from ServQual and Customer Satisfaction instruments. Using the mean scores, Cronbach Alpha, correlation matrix, and regression analysis, the findings indicated moderate positive perceptions of overall university quality service and satisfaction with a low level of satisfaction for some dimensions of quality service such as empathy and assurance. This gap can be minimized by improving the issues of trust, courtesy, and responsiveness of university service with more focus on the emotional aspects and human connection in delivery service.